Improved Gene Targeting through Cell Cycle Synchronization. - Vasiliki Tsakraklides; Elena Brevnova; Gregory Stephanopoulos; A Joe Shaw (PLoS ONE, 2015)
Gene targeting is a challenge in organisms where non-homologous end-joining is the predominant form of recombination. We show that cell division cycle synchronization can be applied to significantly increase the rate of homologous recombination during transformation. Using hydroxyurea-mediated cell cycle arrest, we obtained improved gene targeting rates in Yarrowia lipolytica, Arxula adeninivorans, Saccharomyces cerevisiae, Kluyveromyces lactis and Pichia pastoris demonstrating the broad applicability of the method. Hydroxyurea treatment enriches for S-phase cells that are active in homologous recombination and enables previously unattainable genomic modifications.